الكشف عن معالم الانثروبولوجياالكولونياليةفي شمال افريقيامن خلال مؤلفات مالك بن نبي. - بن محمد, توفيق (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
Talking about anthropology, meanstalking about culture. WhetherArabsocieties know "anthropology" preceded by the discovery of a "culture" in the scientificsense. For thisreason, I have sought to examine the meaning of "culture" in the pole of modernity in Maghreb societies in theirhistorical and social specificities, and theirArab-Islamic affiliation… In hiswritings, Malik bin Nabi found a new culture in the history of Maghreb, a presenceoutside the field of lighthouse, as he put it, a termcommonamongArabtribes, in whatdoes not suggest the sense... The waves of sand, impact the behavior, reflected in the treatment of them, coupledwith the need to maintain the survival. The Koranictext in the meaning, as stated by the Western researcher ...